2014
DOI: 10.1371/journal.pone.0113385
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Association of Smokeless Tobacco and of Betel Quid without Tobacco with Incidence of Oral Cancer in South Asia and the Pacific

Abstract: AimThis systematic review and meta-analysis aimed to critically appraised data from comparable studies leading to quantitative assessment of any independent association between use of oral smokeless tobacco in any form, of betel quid without tobacco and of areca nut with incidence of oral cancer in South Asia and the Pacific.MethodsStudies (case control and/or cohort) were identified by searching Pub Med, CINAHL and Cochrane databases through June 2013 using the keywords oral cancer: chewing tobacco; smokeless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
125
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(132 citation statements)
references
References 74 publications
6
125
0
1
Order By: Relevance
“…Two thirds of the global burden of these cancer cases occur in developing countries, with the Indian subcontinent accounting for one third of the global burden of cancers of the lip and oral cavity [3] . The incidence rates for cancer of the lip, oral cavity and pharynx (C00-14, excluding C11) as well as the larynx (C32) are increasing among women globally, which could be due to access to better diagnostic aids or changes in the socially acceptable behaviour pattern among women in many other parts of the world such as India [32,33] . Apart from the traditional risk factors discussed above, it has been suggested that oestrogen deficiency may influence susceptibility to oral cancer (C00-06) in women; significantly younger mean age at menopause and higher rates of hysterectomy may influence the high rates of oral cancer reported among younger females [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Two thirds of the global burden of these cancer cases occur in developing countries, with the Indian subcontinent accounting for one third of the global burden of cancers of the lip and oral cavity [3] . The incidence rates for cancer of the lip, oral cavity and pharynx (C00-14, excluding C11) as well as the larynx (C32) are increasing among women globally, which could be due to access to better diagnostic aids or changes in the socially acceptable behaviour pattern among women in many other parts of the world such as India [32,33] . Apart from the traditional risk factors discussed above, it has been suggested that oestrogen deficiency may influence susceptibility to oral cancer (C00-06) in women; significantly younger mean age at menopause and higher rates of hysterectomy may influence the high rates of oral cancer reported among younger females [34] .…”
Section: Discussionmentioning
confidence: 99%
“…The association of these components with oral carcinogenesis remains unclear. Areca nut and its component arecoline, a nicotinic acid-based alkaloid, have been reported to promote oral cancer and precancerous lesions (5). Areca nut extract and arecoline induce the upregulation of various growth factors, enzymes and other molecules associated with oral submucous fibrosis, a precancerous condition (6), and stimulate oral cancer cells and immortalized cell lines to express molecules associated with cancer progression (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Among these diversified components, AN is the indispensable constituent of BQ, which is also regarded as a human carcinogen . In addition to oral submucous fibrosis, a recent systematic review and meta‐analysis studies showed that AN usage is positively correlated with oral cancer . Thus, mechanisms of AN‐mediated cell responses are important to uncover the pathology of AN‐associated diseases and worthy to be investigated.…”
Section: Introductionmentioning
confidence: 99%